Influence of Sowing Time on the Quality and Micronutrient Contents of Bread Wheat (Triticum aestivum L): A Recent Study - . Aashu; Y. P. S. Solanki; Divya Phougat; Tanya Barpanda (Research Highlights in Agricultural Sciences Vol. 3, 2022)
Background: Wheat is a staple crop that feeds millions of people, but its productivity is significantly reduced under high temperatures. Maintaining grain quality under climate change is critical for human nutrition, end - use functional properties and commodity value. Objectives: The current study aimed at evaluating the performance of 48 genotypes of wheat under two environments i.e timely and late sown conditions, for assessment of mean performance, variability, correlation, and path analysis of quality and micronutrient traits. Research Methodology: The research was carried out in the experimental area of the Wheat and Barley Section, Department of Genetics and Plant Breeding, CCSHAU, Hisar during 2019-20. The assessment was done for 48 wheat genotypes under two temperature levels (timely and late sown environment) in RBD design with three replications. Results: Heat stress caused a significant reduction in grain yield, grain appearance score, hectoliter weight, sedimentation value, iron and zinc content whereas an increase in crude protein, total gluten content, wet gluten content and total soluble sugar. In the present study, total soluble sugar, wet gluten content, total gluten content showed the highest values of variability, heritability and genetic advance as % of mean and thus are the most important quantitative traits to be taken into consideration for effective selection. A positive correlation was seen between grain yield and hectoliter weight in timely sown environment. Path analysis revealed the highest positive direct effect for hectoliter weight and sedimentation value in timely sown condition, while sedimentation value and iron content for late sown environment and thus in the process of selection much attention should be given to them as these characters are helpful for indirect selection. Conclusion: A negative association between high yield and good quality should be an important target for the next breeding efforts or to determine a quality parameter that performs consistently in both environments.